2007
DOI: 10.1016/j.rmed.2007.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of non-thyroidal illness syndrome in chronic obstructive pulmonary disease

Abstract: Non-thyroidal illness syndrome (NTIS) is frequently detected in chronic, systemic diseases. The objectives of the current study is to assess the alterations of thyroid hormones during exacerbation period, recovery of exacerbation and stable phase of chronic obstructive pulmonary disease (COPD) and correlates of these hormonal alterations. A total of 83 stable COPD patients, 20 patients with acute exacerbation and 30 control subjects were evaluated. TT3, fT3, TT3/TT4 levels of both stable and exacerbation COPD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0
13

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 31 publications
6
46
0
13
Order By: Relevance
“…BMI doesn't correlate with severity of disease. This is in agreement with Karadag F et al and Yumin Zhou et al 5,6 There was highly significant difference was seen in mid arm circumference between COPD cases and control group (p<0.001). But there was a significant difference between moderate to severe and very severe and no significance observed between severe to very severe group of COPD patients.…”
Section: Discussionsupporting
confidence: 91%
“…BMI doesn't correlate with severity of disease. This is in agreement with Karadag F et al and Yumin Zhou et al 5,6 There was highly significant difference was seen in mid arm circumference between COPD cases and control group (p<0.001). But there was a significant difference between moderate to severe and very severe and no significance observed between severe to very severe group of COPD patients.…”
Section: Discussionsupporting
confidence: 91%
“…In critically ill patients as well as those under outpatient care, NTIS has been associated with increased proinflammatory markers [9,22,23]. Pro-inflammatory cytokines such as tumour necrosis factor-α [24], interleukin-1 [25] and 6 (IL-6) [26] have a major role in thyroid hormone imbalances.…”
Section: Discussionmentioning
confidence: 99%
“…A body of evidence suggests that the stimulation of the immune system also induces down-regulation of the hypothalamus-pituitary-thyroid (HPT) axis and related changes in thyroid hormone metabolism, resulting in low circulating levels of T 3 and T 4 hormones (Karadag et al, 2007;Warner and Beckett, 2010). Accordingly, Castro et al (2013) reported that the continuous intravenous infusion of 3.5 to 5.0 µg of LPS kg −1 BW per hour for 48 h induced a reduction in T 3 and T 4 levels in serum and in specific tissues, including heart, liver, kidney cortex, and skeletal muscle.…”
Section: Neuroendocrine Adjustmentsmentioning
confidence: 99%